Survey on Student School Spaces: An Inclusive Design Tool for a Better School - Coelho, Carolina (2022)
This paper presents interdisciplinary research focused on the collaborative redesign in schools, in which an inclusive design tool was created for assessing student feedback on their school spaces and considering it as input for creating a better learning environment. It was developed by a research team using a participatory approach in schools drawn from architecture, geography, and educational sciences, to provide a comprehensive and intertwined approach to school spaces, communities and learning activities. The “Survey on Student School Spaces” (S3S) tool and its methodology are described here, which is a combination of two procedures: a questionnaire and a walkthrough. The first engages a far-reaching sample of participants and makes use of an online platform, while the latter details and justifies those outputs and involves visiting the school with the participants. The S3S pilot study was implemented in two partner schools, which act as the first project case studies. The data provided by this tool acted as the basis for the design proposal for one of the case studies, which included the students’ feedback and involved all the community in the school’s refurbishment. Finally, a discussion was held on the outputs achieved that may contribute towards a participatory design approach in other schools, the validation of the tool per se, and its potential future development and application.